PELATIHAN KETERAMPILAN KOMUNIKASI DALAM PENINGKATAN PELAYANAN BAGI SISWA DI SEKOLAH SMK NEGERI 14 MEDAN - Banjarnahor, Susy Christina; Simamora, Sarah Betty T.; Fazira, Aziza (LPPM Institut Teknologi dan Bisnis Kristen Bukit Pengarapan, 2024)
This study aims to improve the quality of service at SMK Negeri 14 Medan through communication skills training for all educators and education personnel. This training focuses on improving the ability to communicate effectively, both verbally and in writing, as well as the ability to build good interpersonal relationships with students. This training involves various methods such as lectures, group discussions, role-playing, and case studies. The results of the study indicate that the training model developed is effective in improving the communication skills of training participants. In addition, this training model is also considered practical and can be applied in other schools